#### Answer

x = 2

#### Work Step by Step

$\frac{6}{4-3x}$=-3
(4-3x)$\frac{6}{4-3x}$=-3(4-3x)
(4-3x)$\frac{6}{4-3x}$=-3(4-3x)
6=-12+9x
6+12=9x
18=9x
x=2
Check the solution 2
$\frac{6}{4-3x}$=-3
$\frac{6}{4-3*2}$=-3
$\frac{6}{-2}$=-3
-3=-3

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

x = 2

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.